1993
DOI: 10.1103/physrevd.48.2502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of friction on cosmic strings

Abstract: We study the evolution of cosmic strings taking into account the frictional force due to the surrounding radiation. We consider small perturbations on straight strings, oscillation of circular loops and small perturbations on circular loops. For straight strings, friction exponentially suppresses perturbations whose co-moving scale crosses the horizon before cosmological time $t_*\sim \mu^{-2}$ (in Planck units), where $\mu$ is the string tension. Loops with size much smaller than $t_*$ will be approximately c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 17 publications
1
101
0
Order By: Relevance
“…One is phase transition involving violent processes like bubble collision [9,10,11] or the collapse of string loops [12,13,14,15]. As we will see in the next section, however, both scenarios have difficulties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is phase transition involving violent processes like bubble collision [9,10,11] or the collapse of string loops [12,13,14,15]. As we will see in the next section, however, both scenarios have difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to realize large density fluctuations leading to the PBH formation. One is the phase transition which leads to violent processes like bubble collision [9,10,11] or the collapse of string loops [12,13,14,2 As pointed out in Ref. [29], the Bondi solution becomes invalid for the PBH of mass M BH > ∼ 10 4 M ⊙ .…”
Section: Pbh Formation and Observational Constraintsmentioning
confidence: 99%
“…In this case, the probability of PBH formation at a given epoch is determined by the nature and evolution of the perturbations. (3) The collapse of cosmic string loops (Caldwell & Casper 1996;Garriga & Sakellariadou 1993;Hawking 1989;Polnarev & Zembowicz 1991;MacGibbon et al 1998). Due to frequent collisions and reconnections, cosmic strings may occasionally form loops compact enough that the loop is within its Schwarzschild radius in every dimension.…”
Section: Primordial Black Hole Productionmentioning
confidence: 99%
“…We have apparently neglected to consider the loops formed along with the long strings at the time of the cosmological phase transition. These loops, as has been recently shown in [18], may be smoothed by the friction with the cosmological fluid [25]. The loops most smoothed by the friction, however, have Schwarzschild radii smaller than the string thickness; these loops will not collapse to form black holes.…”
Section: Production and Evolution Of Black Holes From The Collapmentioning
confidence: 79%
“…The work of Garriga and Vilenkin [18] considered nucleated cosmic string loops, which may collapse to form black holes. The behavior of classical fluctuations on the loops were examined, and it was shown that while transverse perturbations maintain constant amplitude as the cosmic string loop contracts, radial perturbations shrink by a factor of the perturbation mode number.…”
Section: Collapse Of Cosmic String Loopsmentioning
confidence: 99%